Recent Advances in Electrical Engineering and Control Applications - Chadli, Mohammed; Bououden, Sofiane; Zelinka, Ivan.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book of proceedings includes papers presenting the state of art in electrical engineering and control theory as well as their applications. The topics focus on classical as well as modern methods for modeling, control, identification and simulation of complex systems with applications in science and engineering. The papers were selected from the hottest topic areas, such as control and systems engineering, renewable energy, faults diagnosis-faults tolerant control, large-scale systems, fractional order systems, unconventional algorithms in control engineering, signals and communications. The control and design of complex systems dynamics, analysis and modeling of its behavior and structure is vitally important in engineering, economics and in science generally science today. Examples of such systems can be seen in the world around us and are a part of our everyday life. Application of modern methods for control, electronics, signal processing and more can be found in our mobile phones, car engines, home devices like washing machines is as well as in such advanced devices as space probes and systems for communicating with them. All these technologies are part of technological backbone of our civilization, making further research and hi-tech applications essential. The rich variety of contributions appeals to a wide audience, including researchers, students and academics. .
Keywords: Control engineering; Telecommunication; Signal processing; Control and Systems Theory; Communications Engineering, Networks; Signal, Speech and Image Processing